Regional Integration in South America - Arestis, Philip; Ferrari-Filho, Fernando (Revista Venezolana de Análisis de Coyuntura, 2013)
This contribution attempts to answer two specific questions: First, is the Union of South America Nations (UNASUR) the most viable institution to achieve a consistent regional integration process in South America? Second, what model of regional integration should be adopted in thecase of UNASUR, which would ensure macroeconomic stability and avoid financial and exchange rate crises in South America? The answers to these questions rely on the following objectives: (i) it aims to show that the European Monetary Union is not a project suitable to prevent disruptive economic situations in the South American countries; and (ii) it presents a proposal forthe UNASUR. Resumen Integración Regional en América del Sur Esta contribución trata de responder a dos preguntas: En primer lugar, ¿es laUnión de las Naciones de América del Sur (UNASUR), la institución más viable para lograr un proceso coherente para la integración regional de América del Sur? En segundo lugar, ¿qué modelo de integración regional debería adoptarse en el caso de que UNASUR garantizara la estabilidad macroecónomica y evitara las crisis financiera y cambiaria de América del Sur? Las respuestas a estas preguntas se basan en los siguientes objetivos: (i) demostrar que la Unión Monetaria Europea no es un proyecto adecuado para América del Sur y (ii) presentar una propuesta para la UNASUR.